Management of disputes in the construction industry - Sng, Hock Ling. (2008)
Claims and disputes are undesirable by-products of the evolving construction industry. The negative impacts that they bring about range from strained working relationships, loss of productivity, to wastage of time and money to resolve cases that should not have been there.